Determinan Tax Avoidance pada Perusahaan Property dan Real Estate - Arianti, Baiq Fitri; Siarwi, Siarwi (Gorontalo Accounting Journal, 2025)
This study aims to examine and analyze the factors influencing tax avoidance, including capital structure, financial distress, and good corporate governance. The research method used is a quantitative method with a descriptive statistical approach. The data analysis method employed is panel data regression analysis using E-Views 13. The sampling technique used is purposive sampling, consisting of 14 property and real estate companies listed on the Indonesia Stock Exchange during the 2018–2023 period, resulting in 84 financial statement data points. The results of the study indicate that, partially, capital structure has no significant effect on tax avoidance; financial distress has a positive and significant effect on tax avoidance; and good corporate governance has no effect on tax avoidance. Meanwhile, simultaneously, capital structure, financial distress, and good corporate governance have a significant influence on tax avoidance. The implications of this study are important for stakeholders to maintain the financial stability of companies, enhance supervision of firms experiencing financial distress, and consider these aspects in investment decision-making.